Penerapan Teknik Penyimpanan untuk Meningkatkan Kemampuan Penjumlahan Bilangan Pada Anak Tunagrahita Ringan di SLB Kasih Angela Bitung - Femmy G. Rumampuk (Peneliti.net, 2020)
This research is an attempt to solve the problems faced by mildly disabled students in class IV SLB Kasih Angela Kota Bitung in learning mathematics. This is done through a storage technique based on place values ​​and memories combined with real objects. This research is a Classroom Action Research (CAR) with the subject of 2 mild mental retardation students. Data collection was done by using test techniques. The data analysis shows that there is a positive response and the student's absorption ability is quite good, the average achievement is above 75%. The results of this CAR showed that the storage technique combined with real objects had an effect on the response and absorption of mild mental retardation students in learning mathematics in the addition aspect.